Comparison of Cauchy’s Integral Formula and the Residual Theorem to Find the Integral Value of Complex Functions - Aml Ali (AlQalam Journal of Medical and Applied Sciences, 2023)
This research focuses on the integration of complex function and explores methods for solving them through Cauchy’s integral theorem. The theorem fundamentally depends on whether the function being integrated is analytic. If the function is analytic on and inside any closed curve then. However, the key question arises: what is the value of the integral if the function is not analytic and has an isolated singularity at appoint and closed curve lies entirely within a circle centered at this point, the integral of the function around C can be determined using cauchy’s integral formula and the residue theorem. This study gathered data from books, international references, and academic journals the findings confirm that the residue theorem serves as a generalization of cauchy’s theorem, encompassing various cases: A-Cauchy’s and Cauchy-Goursat theorems, which apply when the function is analytic then. B-Cauchy’s hntegral formula and its ertension via the vesidue theorem, which handle situations where the function has a finite number of isolated singularities. When multiple poles are present, Cauchy’s integral theorem may not be directly applicable, but the residue theorem can be used to solve the integral. هذا البحث يهتم بدراسة تكامل الدوال المركبة و طرق حلها باستخدام نظرية كوشى للتكامل المحدد ,هذه النظرية تعتمد في أساسها على كون الدالة المكاملة تحليلية أم لا, اذا كانت الدالة تحليلية على و داخل أى منحنى مغلق c فان , غير أن السؤال المهم ما قيمة التكامل اذا كانت الدالة المكاملة ليست تحليلية و كانت للدالة نقطة شاذة معزولة عند النقطة و المنحنى المغلق c يقع بكامله داخل دائرة مركزها هذه النقطة فيمكن ايجاد قيمة التكامل للدالة حول المنحنى c باستخدام صيغتا كوشي التكاملية و نظرية البواقي , و اعتمدت هذه الدراسة علي جمع البيانات من الكتب و المراجع الدولية و المجلات البحثية و التي توصلنا الى نتائج تؤكد أن النظرية الاساسية للبواقي تمثل صورة عامة لنظرية كوشي حيث أنها تشمل جميع الحالات: أ-نظرية كوشي و كوشي جورسات, أي الحالة التي تكون فيها الدالة المكاملة تحليلية و بالتالي . ب-صيغة تكامل كوشي و تعميمها, أو النظرية الاساسية للبواقي أي الحالة التي يكون فيها الدالة المكاملة عدد منتهي من النقاط الشاذة المعزولة. اذا تعددت الاقطاب في هذه الحالة لايمكن تطبيق تكامل كوشي مباشرة و أحيانا لا نستطيع تطبيقها , بينما يمكن تطبيق نظرية البواقي